Moving millions with the Mumbai Metro. - Saxena, Sharad (Metro Manila, Philippines Asian Development Bank, 2019)
Catering to more than 7.5 million passengers each day, Mumbai suburban railway system is not only the world most crowded, it is also unsafe and slow. Approved in early 2019, the ADB financed Mumbai Metro Rail Systems Project will include 58 kilometers of new elevated metro rail lines as well as energy efficient, driverless trains. The brief also provides details about the project and contextual information on public transport issues in Mumbai and the governments plans to create a new metro system.
Keywords: Public transport -- India; Road safety behavior; Electronic books